Comparison of Retzius-sparing robot-assisted laparoscopic radical prostatectomy vs standard robot-assisted radical prostatectomy: a meta-analysis - Yu-Li Jiang; Gao-Feng Zheng; Ze-Peng Jiang; Zhen-Li; Xie-Lai Zhou; Jin Zhou; Chun-Hua Ye; Kang-Er Wang (BMC Urology, 2020)
Abstract Background To compare the postoperative continence and clinical outcomes of Retzius-sparing robot-assisted laparoscopic radical prostatectomy (RS-RALP) with non-RS RALP for patients with prostate cancer. Methods We searched PUBMED, EMBASE and the Cochrane Central Register from 1999 to 2019 for studies comparing RS-RALP to non-RS RALP for the treatment of prostate cancer. We used RevMan 5.2 to pool the data. Results A total of seven studies involving 1620 patients were included in our meta-analysis. No significant difference was found in positive surgical margins (PSM), bilateral nerve-sparing, postoperative hernia, complications, blood loss, or operative time. Postoperative continence was better with RS-RALP compared with non-RS RALP (OR = 1.02, OR: 2.86, 95% CI 1.94–4.20, p < 0.05). Conclusions RS-RALP had a better recovery of postoperative continence than non-RS RALP. The perioperative outcomes were comparable for the two methods.